A gamified marketing strategy to create emotional customer connection: Success factors for irresistible advergame design. Issue 1 (29th October 2020) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: This research paper concentrates on deploying advergames to engage customers in a brand's ecosystem of products. The results urged advergame designers to pay attention to four concepts, in descending order of importance: game design, technical elements like multiplayer chat, player personalization, and brand/product-related factors such as integrating product comparisons into the game. To create maximum value from an advergame project, it's recommended that forming an emotional connection between the player and the brand should be the ultimate aim for anyone working on advergames. Originality/value: The briefing saves busy executives, strategists and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.